We Need Both Evidence and Values to Navigate Uncertainty - Upshur, Ross E.G. (The Hastings Center report, 2014)
A commentary on “Ethics and Evidence in Medical Debates: The Case of Recombinant Activated Factor VII,” by Narcyz Ghinea, Wendy Lipworth, Ian Kerridge, Miles Little, and Richard O. Day, in the March-April 2014 issue.